Astaxanthin delays brain aging in senescence-accelerated mouse prone 10: inducing autophagy as a potential mechanism. (4th May 2023) - Fu, Min; Liang, Xiaoshan; Zhang, Xuguang; Yang, Mingzhe; Ye, Qi; Qi, Yuxuan; Liu, Huan; Zhang, Xumei
ABSTRACT: Brain aging is a complex biological process often associated with a decline in cognitive functions and motility. Astaxanthin (AST) is a strong antioxidant capable of crossing the blood–brain barrier. The effect of AST on brain aging and its physiological and molecular mechanism are still unclear. The study aimed to investigate whether AST from AstaReal A1010 improved brain aging by inducing autophagy in SAMP10 mice. Different concentrations of AstaReal A1010 were intragastrically administered to 6-month-old SAMP10 mice for 3 months. The results demonstrated that AST delayed age-related cognitive decline, motor ability and neurodegeneration, upregulated the expression levels of autophagy-related genes beclin-1 and LC3 in the brain. It may induce autophagy by regulating IGF-1/Akt/mTOR and IGF-1/Akt/FoxO3a signaling. Treatment with autophagy inhibitor 3-methyladenine (3MA) partly reversed the anti-aging effect of AST. In conclusion, our findings suggest that AST may induce autophagy by regulating IGF-1/Akt/mTOR and IGF-1/Akt/FoxO3a signaling, thereby delaying age-related neurodegeneration and cognitive decline in SAMP10 mice.